ANALYSIS OF HOUSING LOCATION SELECTION IN TSUNAMI PRONE AREAS CASE STUDI: PADANG UTARA SUB-DISTRICT, PADANG CITY - ika dwi melisa (Optimum: Jurnal Ekonomi dan Pembangunan, 2019)
In line with urban development based on disaster mitigation, the Eastern region of Padang City was developed as a residential area and education center, while the West region adjacent to the coast is an urban commercial area and business center. The transfer of the government center of Padang City to the East (Air Pacah, Koto Tangah District) in 2010 was one of the efforts to reduce the concentration of the population in the coastal area. After the earthquake and tsunami issue in 2009, it was seen changes and displacement of the population towards the east of the city with higher topographic conditions from the center of Padang City adjacent to the Indian Ocean. Based on BPS data from Padang City, in Padang Utara Subdistrict from 2009 to 2010 there was a decline in population, but in 2010 to 2015 there was a significant increase in population. Based on the City of Padang RTRW for 2010-2030, North Padang District is a tsunami prone area. From the above problems, it is important to conduct a study of the selection of housing locations in tsunami-prone areas with Research Question whether the variable price of rental housing, transportation costs and income of the head of household are considered the choice of housing location after the tsunami threat. Based on the results of the analysis, the variables of house rent, transportation costs and income of the family head influence the choice of home locations in tsunami-prone areas.